Tooth loss in individuals under periodontal maintenance therapy: prospective study - Telma Campos Medeiros Lorentz; Luís Otávio Miranda Cota; José Roberto Cortelli; Andréia Maria Duarte Vargas; Fernando Oliveira Costa (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This prospective study aimed to evaluate the incidence, the underlying reasons, and the influence of predictors of risk for the occurrence of tooth loss (TL) in a program of Periodontal Maintenance Therapy (PMT). The sample was composed of 150 complier individuals diagnosed with chronic moderate-severe periodontitis who had finished active periodontal treatment and were incorporated in a program of PMT. Social, demographic, behavioral and biological variables were collected at quarterly recalls, over a 12-month period. The effect of predictors of risk of and confounding for the dependent variable TL was tested by univariate and multivariate analysis, as well as the underlying reasons and the types of teeth lost. During the monitoring period, there was a considerable improvement in periodontal clinical parameters, with a stability of periodontal status in the majority of individuals. Twenty-eight subjects (18.66%) had TL, totaling 47 lost teeth (1.4%). The underlying reasons for TL were: periodontal disease (n = 34, 72.3%), caries (n = 3, 6.4%), prosthetic reasons (n = 9, 19.2%), and endodontic reasons (n = 1, 2.1%). Additionally, subjects with 10% of sites with probing depth between 4 and 6 mm were 5 times more likely to present TL (OR = 5.13, 95% CI 2.04-12.09). In this study, the incidence of TL was small and limited to few individuals. Additionally, gender and severity of periodontitis were significantly associated with TL during the monitoring period.